The The sectoral-regional structure of the wages in Mexico - Valdez-Ramírez, Rolando Israel; Sobrevilla, Verónica (Papeles de Población, 2021)
he present study analyses the sectoral and the regional structure of the wages in Mexico. We exploit a pooled data model with information from the National Occupation and Employment Survey (ENOE) from 2005 to 2018. The results show generalized discrimination against women in all economic activities and regions of the country. The education return on wage differentiates among economic activities, and overall, it is more profitable for women. In professional services, an additional year of education increases 8.4 per cent the salary; in restaurants and lodging services, this return is 3.9 per cent. This study also shows that education is more profitable in the northeast than in other parts of the country. Wages in agriculture in the north double the wages in agriculture in the south. One of the main implications of this study is that education is a crucial instrument for narrowing the gap between women’s and men’s wages.